A sentinel case of penile calciphylaxis in end-stage renal disease: Focus on mortality predictors - Shubhankar, Gautam; Panwar, Vikas Kumar; Saxena, Siddharta (Indian Journal of Case Reports, 2026)
Penile calciphylaxis is a rare yet devastating vascular complication of end-stage renal disease (ESRD) on chronic dialysis, marked by arterial calcification, ischemic necrosis, and a mortality rate exceeding 60%. We report a male in his early forties with ESRD on hemodialysis who presented with dry gangrene of the glans penis. Imaging revealed extensive vascular calcification from the iliac to penile arteries, with markedly elevated calcium–phosphate product, hypoalbuminemia, and secondary hyperparathyroidism. Partial penectomy was performed, but the patient succumbed to systemic complications within 3 weeks. This case underscores the grave prognosis associated with penile calciphylaxis, particularly when accompanied by hypoalbuminemia, elevated calcium–phosphate product, and diffuse vascular involvement. Prompt recognition of such predictors, aggressive metabolic correction, and patient education are crucial to improving survival in this otherwise fatal condition.